(Hexamethylbenzene)Ru catalysts for the Aldehyde-Water Shift reaction. Issue 4 (28th January 2021) - Phearman, Alexander S.; Moore, Jewelianna M.; Bhagwandin, Dayanni D.; Goldberg, Jonathan M.; Heinekey, D. Michael; Goldberg, Karen I.
Abstract : The Aldehyde-Water Shift (AWS) reaction uses H2 O as a benign oxidant to convert aldehydes to carboxylic acids, producing H2, a valuable reagent and fuel, as its sole byproduct. Abstract : The Aldehyde-Water Shift (AWS) reaction uses H2 O as a benign oxidant to convert aldehydes to carboxylic acids, producing H2, a valuable reagent and fuel, as its sole byproduct. (Hexamethylbenzene)Ru II complexes are demonstrated to have higher activity and selectivity (up to 95%) for AWS over disproportionation than previously reported catalysts.